Cognitive cities : second International Conference, IC3 2019, Kyoto, Japan, September 3-6, 2019, Revised selected papers /: second International Conference, IC3 2019, Kyoto, Japan, September 3-6, 2019, Revised selected papers. (2020) - Unknown
No abstract available